Triage; evolution or extinction - Hughes, Geoff (BMJ Group, 2006)
It is generally accepted that the concept of triage began in the military context. It was used in the battlefield to focus limited medical resources on the injured soldiers who were most likely to benefit, ignoring those casualties close to death or with untreatable injuries. It was an early (and possibly the first) example of large scale clinical risk management.